Pendampingan Program Makan Bergizi Gratis Berbasis Posyandu untuk Mendukung Perbaikan Status Gizi Balita di Payaraman Ogan Ilir - Muhammad Kurniawan; Rizqy Akbar Maulana; Ahmad Faisal; Rara Viona; Ahmad Ghiffari; Juan Carlos Vareron; Angga Saputra; Aditia Aditia; Aini Angel Mareta Voniska; Rajip Agusti Hamid; Nanda Asra Agustia; Zahra Sirahmi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Nutritional problems among toddlers require interventions that extend beyond food provision to include growth monitoring and family assistance. This community service program aimed to support the implementation of the Free Nutritious Meal Program (MBG) to improve the nutritional status of toddlers at the Posyandu in Payaraman Timur, Payaraman District, Ogan Ilir Regency. The program was conducted for one month and involved 37 toddlers through recipient registration, anthropometric monitoring, assistance during Posyandu services, and nutrition education for parents. A total of 30 toddlers (81.08%) actively participated in the program. Following the intervention, the number of toddlers with good nutritional status increased from 18 to 22, while those classified as undernourished decreased from 14 to 11 and those with poor nutritional status decreased from five to four. The mean body weight increased from 10.70 kg to 11.34 kg, representing an average gain of 0.64 kg. These findings indicate a favorable trend in toddlers' nutritional status and growth during the assistance period. Program sustainability should be strengthened through regular anthropometric monitoring, continuous family nutrition education, and enhanced involvement of Posyandu cadres.